A giant fossil Mimarachnidae planthopper from the mid-Cretaceous Burmese amber (Hemiptera, Fulgoromorpha). (September 2018) - Jiang, Tian; Szwedo, Jacek; Wang, Bo
Abstract: Dachibangus trimaculatus sp. nov. of a newly established genus Dachibangus gen. nov. from the Upper Cretaceous Burmese amber deposit is described. It is the largest representative of the family known so far, presenting peculiar morphological characters. This finding corroborates wider distribution of Mimarachnidae and their wider ecological spectrum.